Views of the Qur'an regarding the basic concepts of Islamic education - Ratu Suntiah; Mursidin; Muhammad Alif Ramadhan; Teguh Pamuji; Zahra Nur Azizah (al-Afkar, Journal For Islamic Studies, 2026)
The basic concepts of Islamic education are rooted in the teachings of the Qur'an, Sunnah, and ijtihad, which form a framework for educating individuals in various aspects of life. Islamic education consists of three main concepts: Ta'lim, Tarbiyah, and Ta'dib. The purpose of this paper is to describe the basic concepts of Islamic education. Overall, Islamic education aims to create a balance between the cognitive, affective, and psychomotor aspects of students. Thus, this education not only prepares individuals for worldly life but also for the afterlife. The purpose of this paper is to understand the basic concepts of Islamic education and to outline the overall meaning of each existing concept of Islamic education, with the hope that it will be beneficial for the author and readers.